Vasorin: a newly identified regulator of ovarian folliculogenesis. Issue 4 (5th January 2018) - Rimon‐Dahari, Nitzan; Heinemann‐Yerushalmi, Lia; Hadas, Ron; Kalich‐Philosoph, Lital; Ketter, Dafna; Nevo, Nava; Galiani, Dalia; Dekel, Nava
Abstract : Members of the TGF‐β superfamily take part in the control of folliculogenesis. Vasorin (Vasn) is a newly identified negative regulator of TGF‐β signaling whose possible involvement in ovarian physiology has never been studied. Here, we demonstrate that Vasn is expressed in the ovary by somatic cells of follicles, and that its expression is up‐regulated by LH. We established a conditional knockout (cKO) mouse model in which Vasn is deleted specifically in granulosa cells of growing follicles from the secondary stage onwards. Using this model, we show that, upon hormonal stimulation, follicle ovulation size is almost 2‐fold higher. This enhanced ovulatory response is associated with overactivation of the TGF‐β signaling pathway and a lower number of atretic antral follicles. Of importance, we demonstrate that the number of primordial follicles is reduced in prepubertal cKO mouse ovaries, which suggests that the production of VASN by growing follicles protects the ovarian reserve. Finally, analysis of systemic KO mice revealed that the ovarian reserve is almost 2.5‐fold higher, which implies that Vasn may also play a role in primordial follicle formation. Overall, our findings reveal that Vasn is a new regulator that exerts an effect on several key ovarian functions, including folliculogenesis, maintenance of the ovarian reserve, and ovulation.— Rimon‐Dahari, N., Heinemann‐Yerushalmi, L., Hadas, R., Kalich‐Philosoph, L., Ketter, D., Nevo, N., Galiani, D., Dekel, N. Vasorin: a newly identified regulator of ovarian folliculogenesis. FASEB J. 32, 2124–2136 (2018). www.fasebj.org